The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/eva.12239
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental genetic structure and gene flow inDunlin (Calidris alpina), a potential vector of avian influenza

Abstract: Waterfowl (Anseriformes) and shorebirds (Charadriiformes) are the most common wild vectors of influenza A viruses. Due to their migratory behavior, some may transmit disease over long distances. Migratory connectivity studies can link breeding and nonbreeding grounds while illustrating potential interactions among populations that may spread diseases. We investigated Dunlin (Calidris alpina), a shorebird with a subspecies (C. a. arcticola) that migrates from nonbreeding areas endemic to avian influenza in east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 85 publications
(144 reference statements)
0
17
1
Order By: Relevance
“…Furthermore, the high genetic exchanges we observed across geographical populations were consistent with low pairwise differences among populations, supporting Li et al's (2015) argument that high genetic diversity may correspond to weak population structure. Compared with other organisms, birds usually have a lower genetic structure due to their capacity for flight and movements over longer distances , Miller et al 2015a) and geographically unstructured patterns are common in many temperate birds (Zink 1997). None of our results in this study showed any obvious phylogeographical structure across China in this species.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Furthermore, the high genetic exchanges we observed across geographical populations were consistent with low pairwise differences among populations, supporting Li et al's (2015) argument that high genetic diversity may correspond to weak population structure. Compared with other organisms, birds usually have a lower genetic structure due to their capacity for flight and movements over longer distances , Miller et al 2015a) and geographically unstructured patterns are common in many temperate birds (Zink 1997). None of our results in this study showed any obvious phylogeographical structure across China in this species.…”
Section: Discussioncontrasting
confidence: 60%
“…, Miller et al . ) and geographically unstructured patterns are common in many temperate birds (Zink ). None of our results in this study showed any obvious phylogeographical structure across China in this species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of genetic divergence among the snowy plover genetic lineages/demes in microsatellite (F ST = 0.04-0.47), autosomal SNPs (F ST = 0.05-0.58), Z-linked SNPs (F ST = 0.12-0.71) and mtDNA data (Φ ST = 0.03-0.79) is similar to that observed among other plover subspecies, such as the piping plover (Charadrius melodus, Miller et al 2010) and the chestnut banded plover (Charadrius pallidus dos Remedios et al 2017). Genetically, the three snowy plover lineages are more differentiated than the subspecies of some other shorebirds such as dunlin, Calidris alpina, Miller et al 2015) or redshank, Tringa tetanus, Ottvall et al 2005). The differences at microsatellites and mtDNA are also more pronounced than between white-faced plover (Charadrius alexandrinus dealbatus) and Kentish plover (Charadrius alexandrinus), F ST = 0.01, Rheindt et al 2011).…”
Section: Discussionmentioning
confidence: 92%